Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Fictibacillus fluitans sp. nov., isolated from freshwater pond - Yadav, Amit; Maurya, Akanksha; Bhavsar, Yash; Teware, Ruchi; Bhatt, Agrima; DaCosta, Elaine; Thorat, Vipool; Kirdat, Kiran; Dastager, Syed G. (Archives of Microbiology, 2024)
A Gram-positive, aerobic, rod-shaped, spore-forming bacterium, designated NE201(T), was isolated from a freshwater pond in Village Nerur, India. Growth was observed in the range of 15-45 degrees C temperature with optimum at 30 degrees C, pH range of 5-9 (optimum at 7.0), and at concentrations of NaCl ranging between 0 and 14% (optimum 0%, w/v). The 16S rRNA gene sequence showed the highest similarity with Fictibacillus enclensis NIO-1003(T) (JF893461) at 99.01% followed by F. rigui WPCB074(T) (EU939689) at 98.9% and F. solisalsi CGMCC 1.6854(T) (EU046268) at 98.66%. The digital DNA-DNA hybridization (dDDH) and orthoANI values for strain NE201(T) against F. enclensis NIO-1003(T) (GCA_900094955.1) were 33.7% and 87.68%, respectively. The phylogenetic analysis based on the 16S rRNA gene, 92 core genes derived from the genome, and 20 proteins involving over 20,236 amino acid positions revealed the distinct phylogenetic position of strain NE201(T) and the formation of a clearly defined monophyletic clade with F. enclensis. The strain NE201(T) showed a unique carbon utilization and assimilation pattern that differentiated it from F. enclensis NIO-1003(T). The major fatty acids were anteiso -C-15:0 (51.42%) and iso-C-15:0 (18.88%). The major polar lipids were phosphatidylglycerol (PG), phosphatidylethanolamine (PE, and diphosphatidylglycerol (DPG). The antiSMASH analyzed genome of NE201(T) highlighted its diverse biosynthetic potential, unveiling regions associated with terpene, non-ribosomal peptide synthetases (NRPS), lassopeptides, NI-siderophores, lanthipeptides (LAP), and Type 3 Polyketide Synthases (T3PKS). The overall phenotypic, genotypic, and chemotaxonomic characters strongly suggested that the strain NE201(T) represents a novel species of genus Fictibacillus for which the name Fictibacillus fluitans sp. nov. is proposed. The type strain is NE201(T) (= MCC 5285 = JCM 36474).
Keywords: Bacillus; Fictibacillus; Freshwater bacteria